Pemberdayaan Masyarakat Terhadap Pelaksanaan Tugas Kesehatan Keluarga Pada Suku Minangkabau di Desa Nogo Rejo Kec. Galang Tahun 2021 - Fransysca, Helena; Tampubolon, Emelia Apriani (Indonesian Journal Publisher, 2022)
Every family has health duties that aim to prevent health problems and care for sick family members. Family health duties include five main aspects: preventing illness, maintaining health, managing existing illnesses, participating in health programs, and coping with emergency situations. The implementation of these health duties is often influenced by the family culture, including the values and customs of a particular ethnic group. This study focuses on the implementation of family health duties in the Minangkabau community, which is known for its matrilineal kinship system. The population of this study consisted of Minangkabau families in Nogo Rejo Village, Galang Sub-district. The main objective of this study was to identify how Minangkabau families carry out their health duties. The results showed that knowledge about the implementation of family health duties in the Minangkabau community is still limited. This indicates that further research is needed to uncover the cultural factors that influence the implementation of family health duties among the Minangkabau. By digging deeper into family health practices in this cultural context, it is hoped that more appropriate approaches can be found in supporting Minangkabau families in maintaining health and caring for sick family members. This research provides an important basis for further exploration of how Minangkabau cultural values and practices may influence family health. Through a deeper understanding of the relationship between culture and family health, more effective intervention efforts can be designed to improve the quality of life of Minangkabau people.